2013
DOI: 10.1124/dmd.113.055368
|View full text |Cite
|
Sign up to set email alerts
|

Increases in Levels of Epoxyeicosatrienoic and Dihydroxyeicosatrienoic Acids (EETs and DHETs) in Liver and Heart in Vivo by 2,3,7,8-Tetrachlorodibenzo-p-Dioxin (TCDD) and in Hepatic EET:DHET Ratios by Cotreatment with TCDD and the Soluble Epoxide Hydrolase Inhibitor AUDA

Abstract: The environmental toxin and carcinogen 2,3,7,8-tetrachlorodibenzop-dioxin (TCDD, dioxin) binds and activates the transcription factor aryl hydrocarbon receptor (AHR), inducing CYP1 family cytochrome P450 enzymes. CYP1A2 and its avian ortholog CYP1A5 are highly active arachidonic acid epoxygenases. Epoxygenases metabolize arachidonic acid to four regioisomeric epoxyeicosatrienoic acids (EETs) and selected monohydroxyeicosatetraenoic acids (HETEs). EETs can be further metabolized by epoxide hydrolases to dihydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…Therefore, their induction should elevate levels of EETs. This observation was supported by Diani-Moore et al, (2014) who demonstrated that the P450 1A inducer TCDD can increase the production of EETs and its metabolite DHETs in livers of chick embryos. Further, they reported that cotreatment with the sEH inhibitor AUDA increases the ratio of EET: DHET suggesting that stabilizing EETs can alter biology influenced by the epoxides.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Therefore, their induction should elevate levels of EETs. This observation was supported by Diani-Moore et al, (2014) who demonstrated that the P450 1A inducer TCDD can increase the production of EETs and its metabolite DHETs in livers of chick embryos. Further, they reported that cotreatment with the sEH inhibitor AUDA increases the ratio of EET: DHET suggesting that stabilizing EETs can alter biology influenced by the epoxides.…”
Section: Discussionmentioning
confidence: 72%
“…Furthermore, a number of AhR-activators including TCDD and OME increased levels of various epoxy and dihydroxy metabolites in chick embryos (Diani-Moore et al, 2006). This effect was enhanced by combining TCDD with 12-(3-adamantan-1-yl-ureido)-dodecanoic acid (AUDA), a well characterized sEHI (Diani-Moore et al, 2014) suggesting the feasibility of modulating EET levels by augmenting their synthesis through inducing P450s and minimizing their metabolism by sEH inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…Clearly, there are pools of quantifiable intra- and extra-cellular, free acid EpFAs both of which are stabilized and augmented by sEH inhibitors. Tetrachlorodioxin and other xenobiotics induce cytochrome P450 enzymes usually studied for their role in xenobiotic metabolism, sufficiently that they contribute to titers of EpFAs [18]. Since the 2C and 2J as well as a variety of other cytochrome p450s will oxidize multiple unsaturated fatty acids, it is not surprising that the EpFA produced depends in part on the diet as well as the circulating and stored lipids.…”
Section: Novel Paths To Positively Modulating Epfa Titersmentioning
confidence: 99%
“…Alternatively, this could conceivably be due to transport of these metabolites from other organs in the blood. Transport of such metabolites in the circulation is known to occur (Diani-Moore et al 2014). …”
Section: Enzymes Responsible For the Tcdd-mediated Increases In Oxylimentioning
confidence: 99%
“…Previously, Dalton and coworkers showed that TCDD exposure increased the levels of three cyclooxygenase-derived arachidonic metabolites in the urine of mice (Dalton et al 2001). More recently, Diani-Moore and coworkers have reported that TCDD increased the levels of EETs and DHETs in the heart and liver of chick embryos (Diani-Moore et al 2014). …”
Section: Enzymes Responsible For the Tcdd-mediated Increases In Oxylimentioning
confidence: 99%